Expressway to Your Skull. - Guizzo, E. (IEEE spectrum)
One of the crucial technologies in Sony's new PlayStation 3 gaming console is the data transfer connections, or buses, that link the Cell processor to both the console's main memory and the graphics processor. The immersive experience that Sony is aiming for depends largely on the data flowing to and from the Cell processor at speeds way beyond anything achieved in a home-electronics system. The bus between the Cell and the PS3's memory will achieve a peak data-transfer rate, or bandwidth, or 25.6 gigabytes per second. Meanwhile, the bus connecting the Cell to the graphics chip will move data at 35 GB/s, or about five to 10 times what you can get with today's best PC-bus technology. To maintain the integrity of the electrical signals and keep them synchronized because of the higher frequencies required for faster data rates, Sony relies on a signaling technique that minimizes interference and attenuation and a timing mechanism that compensates for time-control discrepancies